Upaya Meningkatkan Motivasi Siswa Dalam Pelajaran Speaking Pada Text Monolog Recount Melalui Model Pembelajaran Picture And Pictures Di Kelas VIII-E SMP N 2 Payakumbuh - Sofia Salmi (PAKAR Pendidikan, 2014)
The purpose of this class action research is to improve student motivation in speaking lesson at monologue recount text. This research is accomplished by using media through learning model picture and pictures. This research was done in three cycles within 6 effective weeks of 3 months period. Each cycle consists of 4 skills, listening, speaking, reading and writing. The implementation of this research is taken twice in a week. The research subject was the students from VIII-E class, SMPN 2 Payakumbuh. The data in this study was collected by using questionare about students learning process activities, observation sheet, and test. Data were analyzed by using quantitative qualitative technique. The conclusions of this study showed an increasing of student motivation in the classroom during the speaking lesson in monologue recount text.